2023
DOI: 10.3389/fmars.2023.1109523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of habitat usage on hypoxia avoidance behavior and exposure in reef-dependent marine coastal species

Abstract: Reef habitat in coastal ecosystems is increasingly being augmented with artificial reefs (ARs) and is simultaneously experiencing increasing hypoxia due to eutrophication and climate change. Relatively little is known about the effects of hypoxia on organisms that use complex habitat arrangements and how the presence of highly preferred AR habitat can affect the exposure of organisms to low dissolved oxygen (DO). We performed two laboratory experiments that used video recording of behavioral movement to explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…Our assertion regarding the significant positive impact of AR construction on the proliferation of this species aligns with observations of the mutual reinforcement between the 'attraction' and 'production' functions within reef areas [6]. While prior studies, such as those by Yu et al [37], Cresson et al [8,38], and Feng et al [39], have notably demonstrated the attraction effect in black rockfish and confirmed the production effects through isotopic technology, our study extends this understanding. We observed a consistent dietary preference among resident black rockfish, indicating a substantial 'production' function, with over 80% exhibiting residency over an extended period.…”
Section: Ecological Functions Of Reef Area For Black Rockfishsupporting
confidence: 89%
See 1 more Smart Citation
“…Our assertion regarding the significant positive impact of AR construction on the proliferation of this species aligns with observations of the mutual reinforcement between the 'attraction' and 'production' functions within reef areas [6]. While prior studies, such as those by Yu et al [37], Cresson et al [8,38], and Feng et al [39], have notably demonstrated the attraction effect in black rockfish and confirmed the production effects through isotopic technology, our study extends this understanding. We observed a consistent dietary preference among resident black rockfish, indicating a substantial 'production' function, with over 80% exhibiting residency over an extended period.…”
Section: Ecological Functions Of Reef Area For Black Rockfishsupporting
confidence: 89%
“…In our field surveys, the inshore area remains shallow (5 m) with lower temperatures in winter, while the reef and offshore areas are deeper (>15 m) with a temperature of 7.6 • C. Considering the spatial distribution of the winter isoscape, the possible sources of the two non-resident individuals might be deeper and in unsampled areas. It is likely that the reef area exerted an 'attraction' function in winter since it provides the rocky substrate known to be chosen by rockfish [37] and abundant food resources.…”
Section: Potential Sources For Non-resident Individualsmentioning
confidence: 99%